Morphometrical diversity of reproductive structures in Hyptis suaveolens (L.) Poit. : an ethnomedicinal weed of Lamiaceae - Saha, Puja Rani; Sinha, Sangram; Sinha, Rabindra Kumar (Current Botany, 2017)
Hyptis suaveolens (L.) Poit. is an invasive ethnomedicinal weed of Lamiaceae. Morphometrical studies of floral structures and seed dimorphism in the species were carried out. Detailed measurements of reproductive structures revealed moderate size variability in morphometric characters. The present study reconfirms the existence of efficient pollination system in protandrous flower with carinal explosion in the species. Characteristic seed dimorphism prevailed with variable nutlet number and sizes in mature fruits. The inconsistent pattern of nutlet distribution in the fruit was grouped into five categories and the most frequent was category A (2+2). Seed germination of H. suaveolens was PEF type. Large seeds showed higher germination rate with 95% under lateritic soil condition whereas small seeds almost lacked germination. The present study highlights the irregular and random nutlet distribution in fruits of H. suaveolens adding to its diversity and fundamental reproductive behaviour. Keywords: Ethnomedicinal weed, morphometry, reproductive structures, Lamiaceae.Â